Hemipelvectomy: Outcome in 84 dogs and 16 cats. A veterinary society of surgical oncology retrospective study. Issue 1 (20th November 2013) - Bray, Jonathan P.; Worley, Deanna R.; Henderson, Ralph A.; Boston, Sarah E.; Mathews, Kyle G.; Romanelli, Giorgio; Bacon, Nicholas J.; Liptak, Julius M.; Scase, Tim J.
<x xml:space="preserve">Abstract</x> Objective To report clinical findings, perioperative complications and long‐term outcome in dogs and cats that had hemipelvectomy surgery for treatment of neoplasia. Study Design Multi‐institutional retrospective case series. Animals Dogs (n = 84) and cats (16). Methods Medical records (January 2000 to December 2009) of dogs and cats that had hemipelvectomy at participating institutions were reviewed. Postoperative progress and current status of the patient at the time of the study was determined by either medical record review, or via telephone contact with the referring veterinarian or owner. Results Complications were infrequent and usually minor. Hemorrhage was the main intraoperative complication; 2 dogs required blood transfusion. One dog developed an incisional hernia. In dogs, hemangiosarcoma had the worst prognosis with a median survival time (MST) of 179 days. MST for chondrosarcoma (1232 days), osteosarcoma (533 days), and soft tissue sarcoma (373 days) were not statistically different. Median disease‐free interval (DFI) for local recurrence of all tumor types was 257 days. Cats had 75% survival at 1 year, which was significantly longer than dogs. Conclusions Survival times for most tumor types can be good, but surgical margins should be carefully evaluated to ensure complete tumor removal. Adjuvant therapies may be advisable particularly for dogs to reduce rates of local recurrence or distant metastasis.